The Social Science of Crisis and the Crisis of Philippine Social Science - David, Randolf S. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
A crisis in its sociological sense, connotes a perception of the existence of a real threat to the values that one holds. This perception may be vague or it may be clear. People search for explanations for those events that are transforming their lives and which they perceive to lie effectively outside their control. They demand perspectives and frameworks within which they can locate events as they unfold and in terms of which they can define their meanings. Is the social science community in the Philippines intellectually and culturally equipped to respond to such urgent needs? There are a number of factors that prevent the Philippine social science community from being able to meaningfully relate itself to these emergent concerns of a society in crisis. The first consideration is that in normal times, social scientists in particular are enlisted by various Establishment agencies to do "developmental social science." The second consideration is what others have called the alienation of the intellectual in general, or of the social science in particular, from the masses. Unless Filipino social scientists as a community consciously confront these conditions and collectively in this critical moment of their people's history.